The Effect of Mendala Interventions on Reduction Anxiety, and Mindfulness (Journal of Social Sciences Review, 2024)
For the purpose of treating a wide variety of psychological issues, art therapy techniques are currently being developed. In a similar vein, the utilisation of mandala art therapy is increasingly acknowledged for its capacity to reduce anxiety and promote mindfulness. The findings of research conducted on mandala art therapy indicate that the utilisation of mandala techniques had a meditative impact on the participants. This allowed them to relax and calm both their bodies and their minds, which ultimately resulted in a reduction in psychological disorders. Within the scope of this study, mandala interventions were implemented on a group of young adults hailing from Pakistan. A decrease in anxiety is indicated by a drop in the mean scores of the variables, with the exception of mindfulness, which displayed a decrease in mean scores. On the other hand, the mandala interventions led to an increase in the amount of mindfulness that was experienced. The findings of this study can be applied to any organisation that deals with issues related to mental health. A coping method that is recommended for anxiety and mindfulness is the use of mandala therapy.
Keywords: Art Therapy; Anxiety; Mindfulness